Stable isotope ratio as a tracer of mangrove carbon in Malaysian ecosystems - Rodelli, M.R.; Gearing, J.N.; Gearing, P.J.; Marshall, N.; Sasekumar, A. (Springer Verlag (Germany), 1984)
The ratio of stable carbon isotopes (δ13C) in plants and animals from Malaysian mangrove swamps, coastal inlets, and offshore waters was determined. Vascular plants of the swamps were isotopically distinct ( x±s.d.=-27.1±1.2‰) from plankton (-21.0±0.3‰) and other algae (-18.7±2.2‰). Animals from the swamps (-20.9±4.1‰) and inlets (-19.8±2.5‰) had a wide range of isotope ratios (-28.6 to-15.4‰), indicating consumption of both mangrove and algal carbon. Several commercially important species of bivalves, shrimp, crabs, and fish obtained carbon from mangrove trees. Mangrove carbon was carried offshore as detritus and was isotopically distinguishable in suspended particulate matter and sediments. Animals collected from 2 to 18 km offshore, however, showed no isotopic evidence of mangrove carbon assimilation, with ratios (-16.5±1.1‰, range-19.1 to-13.1‰) virtually identical to those reported for similar animals from other plankton-based ecosystems. Within groups of animals, isotope ratios reflected intergencric and interspecific differences in feeding and trophic position. In particular, there was a trend to less negative ratios with increasing trophic level.